Four forage sorghum silage additives evaluated - K.K. Bolsen; Jack G. Riley; J.D. Hoover (Kansas Agricultural Experiment Station Research Reports, 1973)
Two trials were conducted to evaluated four forage sorghum silage additives: ammonium iso-butyrate, aureomycin, sodium hydroxide, and a mixture of acetic and propionic acids. A control silage received no additives.
Keywords: Cattlemen' s Day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station); 568; Beef; Forage sorghum; Performance; Crude protein